Gry w rozwijaniu wybranych kompetencji kluczowych dzieci – przegląd literatury przedmiotu - Kondracka-Szala, Marta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The aim of the article was to explore the area of games and gamification in children education, particularly with attention to their key competences. In this paper, the author seek to answer the following question: what is the role of games/gamification in children education process and what are the possibilities of use in this area? by method of literature (polish and foreign) review. The conclusions of the study are significant cognitive and practically. They tend to reflection on the future shape of using games in children education.
Keywords: child education; games; gamification; key competences